Micromechanisms of crack initiation of a Ti-8Al-1Mo-1V alloy in the very high cycle fatigue regime. (September 2021) - Gao, Tao; Xue, Hongqian; Sun, Zhidan; Retraint, Delphine; He, Yanli
Highlights: Very high cycle fatigue properties of a Ti-8Al-1Mo-1V alloy were investigated. Micromechanisms of crack initiation were studied by microscopic observations. Intensive plastic slips induced by VHCF were observed in specimen interior. Crack-initiation occurs with the formation of nano-marking facets and flat facets. Large scatter in fatigue life is caused by slip inhomogeneity in different grains. Abstract: Fatigue behavior and damage mechanisms of a Ti-8Al-1Mo-1V alloy were investigated in the very high cycle fatigue (VHCF) regime. Fracture surfaces and slip morphologies of failed specimens were observed to reveal the crack-initiation micromechanisms. The crack initiation area is characterized by nano-marking facets and flat facets surrounded by tearing topography surface (TTS). The VHCF crack initiation is attributed to the formation of nano-marking facets and flat facets in αp grains induced by dislocations and slip activity. The slip activity is the main micro-deformation mechanism while a large scatter in fatigue life can be attributed to slip inhomogeneity.